Draft Proposals Fourth Five Year Plan Haryana State Volume III - Planning Commission (Planning Commission, 1966)
The provisions under the draft 4th Five year Plan have been based on the spill over works from 3rd Five Year Plan and the Haryana Development Committee, Final Report keeping in view the requirements of development of Irrigation potentials of Haryana State. A brief description sub-head-wise is enumerated.
Government of Haryana Planning Department